Management of benign ovarian cysts in a semiurban hospital: a retrospective study - Sridhar, M.; Susmitha, Chillamherla (International Surgery Journal, 2018)
Background: Benign ovarian cysts are one of the most common cause of surgery. Most of these cysts are asymptomatic and are accidentally found when undergoing a pelvic examination. We conducted a study on the types of benign ovarian cysts in our setup and their surgical management. Methods: 156 patients who were clinically diagnosed and operated on benign ovarian cysts were included into the study. Transvaginal ultrasound was performed in all the patients to assess the size of cysts and other characteristics of the mass and to exclude malignancy. All the cysts were laparoscopically treated. Results: Out of 156 patients, most of the patients (27.9%) had come to the hospital with chronic pelvic pain. 25.3% of the patients were asymptomatic and 14.3% had complaints of pelvic mass. Endometrioma which was seen in more than 50% of the cases followed by dermoid cysts seen in 24.3% of the cases. The most common type of surgery performed on the patients was cystectomy in 85.3% followed by oophorectomy in 10.9% of the cases and in 3.8%, a complete laparoscopic salpingo-oophorectomy was performed. Complications was observed in 1.3% of the cases. Conclusions: Laparoscopic surgery for the removal of benign ovarian cysts the most preferred type of surgery, with cystectomy being the most common type and that with salpingo-oophorectomy being fairly uncommon. As, this is not without complications, careful patient selection and proper surgical experience is required o ensure a safe laparoscopy.